Barriers to effective comunication in an organisation: a case of selected multinational company in Malaysia / Nurazree Mahmud ... [et al.] - Mahmud, Nurazree; Muhammed Zulfikri, Nur Khalisah; Ismail, Irzan; Miskam, Zamri (2020)
Communication effectiveness has been one of important factors in daily life covering workplaces, relationships, and all sorts of human interaction. As a workplace or even learning centres, any organisation shall need to practise good and effective communication, from within and outside organisation, to achieve its goals. Many researchers have developed and shared various theories, models and frameworks with regards to this topic of interest due to its cruciality to be achieved and practised. However, communication is a very broad subject and is affected by many internal and external factors. The internal and external factors may both refer to communication barriers, which could be a stimulus, a situation or even an object that may hinder or prohibit any part of a communication process making it harder for messages to be encoded and decoded precisely by parties involved. The purpose of this research is to investigate the factors influencing effective communication in an organisation. This research is a qualitative research that used questionnaires as the instrument for collection of data. The data was collected and viable at 77% out of 69 respondents which was derived from the total population of 90 elements. Sample selection was based on a non-probability approach. The data collected was then evaluated by using Statistical Package for the Social Science (SPSS) through which numerous tests were converged such as reliability test, normality test, frequency distribution, descriptive analysis and multiple regression analysis. The results indicated that organisational environment affects effective communication more than language and culture do